PENGARUH PENGGUNAAN METODE JARIMATIKA TERHADAP PENINGKATAN DAYA INGAT MENGHAFAL PERKALIAN MATEMATIKA SISWA KELAS III SD - Natasya, Fitri; Nurmayani, Nurmayani; Perangin-angin, Laurensia Masri; Mailani, Elvi; Purnomo, Try Wahyu (Universitas Negeri Medan, 2024)
The low memorization capacity of students in the mathematics subject of multiplication material is caused by several factors, such as learning activities that are still teacher-centered and do not involve students actively, and the learning methods used are less varied. Efforts to improve students' memorization ability are by applying the Jarimatika learning method. This research aims to improve the ability to memorize mathematical multiplications for class III students using the Jarimatika learning method. The method used in this research is quantitative research with Quasi Experimental. From the results of the pretest and posttest for the two research classes, namely the experimental class which was given treatment and the control class which was not given treatment, it can also be seen in the attachment for the scores for each research class, the improvement and the differences between classes given treatment and not given treatment t_count > t_table namely 7.529 > 1.678, then Ho is rejected and Ha is accepted. This shows that there is an influence of using the Jarimatika learning method on increasing memory for memorizing multiplications with the average increase obtained being 42.45% before the Jarimatika learning method was carried out, and 84.85% after the Jarimatika learning method was carried out. Keywords: Memory, Learning Methods, Jarimatika